Psychological Immunity and its Relationship with Self- Esteem among Kindergarten Students of Salahadin University - Mihraban Hussein Saleh; Nian Namiq Sabr (Zanco Journal of Human Sciences, 2026)
The aim of this study is to find out: Level of Psychological immunity and self-esteem among kindergarten students and the relationship between Psychological immunity and self-esteem among students and differences in level of Psychological immunity and self-esteem among students according to) first and fourth( grade and place of residence(city center - outside the city) , The research tool consists of a measure of psychological immunity based on the theory (Olah) and several other literatures created with the measure of self-esteem that the researcher has made material The sample of the research is (100) students, The data collected by the )t.test( for one sample and two samples, and the (Χ²) test, Pearson correlation , The results of the study include the level of Psychological immunity and self-esteem among students is highly , and there is a relationship between Psychological immunity and self-esteem, There is no statistically significant difference between the students regarding the level of psychological immunity based on the study level and place of residence, There is no difference among students according to the variable of study level Regarding self-esteem, but there is a difference among students on their place of residence, with the difference favoring students from outside the city, "At the end of the research, several recommendations and suggestions were presented.